Knowledge, attitudes and behaviour about Sexually Transmitted Infections: a survey among Italian university female students - Chiara De Waure; Alice Mannocci; Chiara Cadeddu; Maria Rosaria Gualano; Giacomina Chiaradia; Daniela Vincitorio; Francesco Di stanislao; Elisabetta De Vito; Antonio Boccia; Walter Ricciardi; Giuseppe La Torre (Epidemiology, Biostatistics and Public Health)
Aims: Improvements have been made in terms of STIs mortality, but young women still have a lack of attention to the STIs prevention. We investigated the knowledge and attitudes about STIs and their prevention among a sample of Italian university female students. Methods: We designed a questionnaire about knowledge and attitudes toward STIs, Papanicolau test (Pap test) and Human Papilloma Virus (HPV) and had it filled out by 285 young women. Chi-square test, Mann-Whitney test and a multivariable analysis were performed in order to identify associated factors.   Results: Knowledge about STIs seems weak, oppositely to knowledge about preventive measures. In line with the results of the univariate analyses, the multivariable one confirmed a higher probability to answer rightly for women who knew the effective behaviours for preventing STIs, women who took information about STIs from Internet, books and TV and those using natural methods (OR 2.77 - 95%CI 1.47-5.23, OR 2.99 - 95%CI 1.62-5.53 and OR 2.55 - 95%CI 1.05-6.18, respectively) and a lower one for students from Cassino and those who knew is possible to recover from STIs (OR 0.38, 95%CI 0.17-0.87 and 0.42, 95%CI 0.20-0.88, respectively). Furthermore, about Pap test it also confirmed the role of a medium-high STIs level of knowledge (OR 2.11, 95%CI 1.02-4.37) and a lower probability to know about it for women from Cassino (OR 0.25, 95%CI 0.09-0.73). Conclusions: Young women are not completely aware of STIs risks and preventive measures. Informational and educational campaigns should be implemented to reach this target group and lighten the current and future burden of STIs.